Self-Awareness and Self-Control: Protective Factors Against Social Media Addiction Tendency among Adolescents - Aulia Puspita; Maria Theresia Asti Wulandari (Universitas Negeri Padang, 2025)
The tendency toward social media addiction is an increasingly prevalent phenomenon, especially among adolescents. High levels of social media use among adolescents may cause various negative impacts, both psychologically and socially. Self-awareness and self-control are associated with the tendency toward social media addiction. Based on this, the present study aims to analyze the influence of self-awareness and self-control on the tendency toward social media addiction among adolescents in Bangka Belitung. The study employed a quantitative approach using a survey method. Participants (N = 470) were adolescents aged 13–19 years residing in Bangka Belitung, with daily social media use either less than or greater than three hours. The sample included 180 males (38.3%) and 290 females (61.7%). Age distribution was 13–15 years (n = 170, 36.2%), 16–18 years (n = 140, 29.8%), and 19 years (n = 160, 34.0%). Three psychological scales were used as the instruments: the social media addiction tendency scale based on indicators from Young and Abreu (2017), the self-awareness scale based on the model by Carden et al. (2021), and the self-control scale based on Averill’s theory (Averill, 1973). Data were analyzed using multiple linear regression to examine the influence of each independent variable on the dependent variable, both simultaneously and partially, to test the hypotheses. The findings revealed that self-awareness significantly influenced the tendency toward social media addiction, as did self-control, which also showed a significant influence. Furthermore, self-awareness and self-control simultaneously had a significant effect on the tendency toward social media addiction among adolescents. These findings underscore the importance of strengthening self-awareness and self-control as key psychological factors in preventing social media addiction. Future studies are expected to employ a longitudinal approach or expand the scope of regions and participant age ranges.